Intuition and the Crisis of Modern Epistemology: Comparative Insights from Mulla Sadra and Henri Bergson for Islamic Education - Mustofa, Aulia; Firdaus, Miftahul; Rasyid, Yusuf Nur Rochman (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to critically examine the role of intuition within the crisis of modern epistemology by conducting a comparative analysis of the philosophical thoughts of Mulla Sadra and Henri Bergson. The research is motivated by the dominance of rational-empirical paradigms in contemporary knowledge systems, which tend to marginalize intuitive and non-discursive modes of knowing. Using a qualitative library research approach, this study applies systematic literature review procedures combined with comparative analysis and content analysis based on Krippendorff’s framework. Primary and secondary sources are critically examined to explore the epistemological structures of intuition in both thinkers. The findings reveal that intuition plays a more fundamental and transformative role in knowledge acquisition than traditionally assumed. Mulla Sadra conceptualizes intuition (‘ilm al-hudhuri) as an ontological and integrative mechanism that unifies reason, revelation, and spiritual experience, thereby producing holistic knowledge. In contrast, Henri Bergson positions intuition as a method of direct experience that enables access to the dynamic nature of reality (durée), functioning as either a dominant or complementary alternative to rational analysis. These differences reflect two distinct epistemological orientations: integrative-transcendental (Sadra) and intuitive-phenomenological (Bergson). The novelty of this study lies in its effort to bridge classical Islamic philosophy and modern Western philosophy within a single comparative epistemological framework, while also situating intuition as a response to the limitations of modern rational-empirical epistemology. This study contributes to the development of an integrative epistemological paradigm by demonstrating that intuition can serve as a foundational dimension of knowledge when harmonized with reason and revelation. Furthermore, it offers significant implications for Islamic education by proposing a holistic framework that integrates cognitive, intuitive, and spiritual dimensions in the learning process.